Overview of the effect of monomers and green solvents on thermoresponsive copolymers: phase transition temperature and surface properties. Issue 106 (13th October 2015) - Reddy, P. Madhusudhana; Chang, Chi-Jung; Hsieh, Shih-Rong; Huang, Hsin-Chun; Lee, Ming-Ching
Abstract : The thermoresponsive and surface properties of PNIPAM based copolymers were investigated in response to green solvents, ionic liquids. Abstract : The present study explores the effect of the monomer substitution pattern of different copolymers on their volume phase transition temperature (VPTT) and surface wetting properties (SWPs) with the aid of differential scanning calorimetry (DSC), contact angle (CA), scanning electron microscopy (SEM) and Fourier transform-infrared spectroscopy (FT-IR) measurements. The present experimental results unveil that the VPTT and SWPs were greatly governed by the ability of the neighboring side chains to form intramolecular hydrogen bonds and the hydrophobic–hydrophilic balance of the polymer. The substitution of some of the acrylic acid (AA) monomers in the copolymer hydrogel P(NIPAM- co -AA) by the polyethyleneglycolmethacrylate (PEGMA) monomer resulted in the copolymer hydrogel, P(NIPAM- co -PEGMA- co -AA). The PEGMA in P(NIPAM- co -PEGMA- co -AA) can promote the intermolecular hydrogen bonds of the copolymer with the water molecules and thus hinders the formation of the intramolecular hydrogen bonds. Consequently, the VPTT of the P(NIPAM- co -PEGMA- co -AA) occurs at higher temperatures when compared to the P(NIPAM- co -AA) and P(NIPAM- co -PEGMA) systems. Further, in view of the potential applications of ionic liquids (IL) in polymer science, the effect of IL on the VPTT and SWP of the copolymers was investigated. The knowledge from this study can pave the way to engineer stimuli responsive polymers for a wide range of applications in the modern era.